THE HISTORICAL SIGNIFICANCE OF THE MYSTERIOUS HETTIC SCRIPT - Husniddin Muhitdinovich Yakubov (Web of Journals Publishing, 2024)
The article discusses the mysterious writing and diplomacy of the Hittite state, which had a rich archive of sources on the history of the Ancient East.
Keywords: Hittites, writing, cuneiform, Hama stones, diplomatic relations, Hattusili III, Bosphorus, Qoratepa.